Efficacy and limitations of systemic corticosteroids in patients with CRSwNP compared to alternative therapies with monoclonal antibodies: real-life of 101 patients from the Lazio region, Italy - Anastasi, F.; Di Nota, C.; Sessi, S.; Marzetti, A.; Sambito, A.; Della Casa, M.; Pizzolante, S.; Bandiera, G. (Frontiers in Allergy, 2025)
Chronic Rhinosinusitis with Nasal Polyps (CRSwNP) is a chronic inflammatory disease. Its severe uncontrolled form may share, with asthma and atopic dermatitis, the pathophysiological mechanism of T helper 2 inflammation, characterized by tissue eosinophilia and high local IgE levels. Comorbidities and the severity of symptoms result in a poor quality of life. CRSwNP is difficult to treat both medically and surgically. Systemic corticosteroids are widely used to manage signs and symptoms of this disease. However, prolonged use of systemic corticosteroids is associated with numerous side effects that limit their long-term use. Alternative therapy with new biologic drugs allows good control of the signs and symptoms of CRSwNP, without the side effects of systemic corticosteroids. Through an interview proposed to patients affected by CRSwNP, the use of systemic corticosteroids, their dosage and the methods of administration were analyzed in the period preceding the start of therapy with biological drugs and the real impact of biological therapy on corticosteroid use.